1993
DOI: 10.1002/eji.1830231023
|View full text |Cite
|
Sign up to set email alerts
|

The G protein‐coupled receptor BLR1 is involved in murine B cell differentiation and is also expressed in neuronal tissues

Abstract: The BLR1 gene, isolated initially from Burkitt's lymphoma cells (Eur. J. Immunol. 1992. 22: 2795), encodes a G protein-coupled receptor with significant relationship to receptors for chemokines (IL-8, MIP-1 alpha) and neuropeptides. The murine homologue of human BLR1 was cloned and used to investigate its expression in vivo. blr1-specific transcripts are observed in secondary lymphatic organs and to a lesser extent in brain of adult mice but not in other tissues. RNA in situ hybridization localizes blr1 transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 47 publications
2
36
0
1
Order By: Relevance
“…Interestingly, we show that CXCR5 is down-regulated in HCL and completely absent in multiple myeloma. This latter observation confirms earlier findings of Fö rster et al using Northern blot hybridisation in murine plasmacytoma cell lines 20 and flow cytometry in one patient with multiple myeloma 13 and extends them to a larger patient cohort. Our data showing weak or even absent staining for CXCR5 on HCL and ALL cells, respectively (Table 1), contrast with those reported by Jones et al, 17 who demonstrated strong CXCR5 immunoreactivity on 30 cases of B cell lymphoma/leukemia corresponding to all maturational stages of B cell development.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we show that CXCR5 is down-regulated in HCL and completely absent in multiple myeloma. This latter observation confirms earlier findings of Fö rster et al using Northern blot hybridisation in murine plasmacytoma cell lines 20 and flow cytometry in one patient with multiple myeloma 13 and extends them to a larger patient cohort. Our data showing weak or even absent staining for CXCR5 on HCL and ALL cells, respectively (Table 1), contrast with those reported by Jones et al, 17 who demonstrated strong CXCR5 immunoreactivity on 30 cases of B cell lymphoma/leukemia corresponding to all maturational stages of B cell development.…”
Section: Discussionsupporting
confidence: 91%
“…The observed 91% homology between mouse and human CXCR4 is exceptionally high for members of the chemokine receptor family as only 83% for homology has been reported for human and mouse BLR1/CXCR5 [29,30], 78% homology for CCR1 [31,32], and 63% for CCR3 [32,33]. Together with the fact that SDF-1 shows 99% identity between both species, one is tempted to speculate that both receptor and ligand might serve identical functions in both species.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is CXCR5 receptor isolated initially from Burkitt's lymphoma cells but expressed also in mature B cells and in brain neurons (Kaiser et al, 1993).…”
Section: Chemokine Receptors In Cns Pathologymentioning
confidence: 99%